Pengaruh Tingkat Pendidikan dan Pengangguran Terhadap Kemiskinan di Indonesia - Purwanti, Monia; Andini, Deli; Nasution, Susanti; Hardiyanti, Livia; Jolianis, Jolianis (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to examine and analyze the impact of education level and unemployment on poverty in Indonesia, both individually and in combination. The research is associative in nature, with Indonesia as the subject of the study. The data used in this research is time-series data for the period 1980-2024, sourced from the World Bank. Data collection was conducted using relevant secondary data. The study tests the hypothesis that lower education levels and higher unemployment rates significantly contribute to the increase in poverty. Multiple linear regression analysis is employed to assess the significant relationship between education, unemployment, and poverty. The findings hold crucial implications for the development of poverty alleviation policies in Indonesia, highlighting the need to focus on enhancing both the quality and accessibility of education, as well as creating integrated programs to address education and unemployment challenges simultaneously. Such an approach is expected to have a more substantial impact on reducing poverty rates.